Association between preoperative inflammatory status via CALLY index and postoperative pneumonia occurrence in resectable esophageal squamous cell carcinoma patients: a retrospective cohort study - Fan, Mengtao; Zhu, Yihan; Qian, Long; Hu, Chuanxian; Ding, Hui (Frontiers in Oncology, 2025)
BackgroundPostoperative pneumonia significantly affects recovery and prognosis in patients with esophageal squamous cell carcinoma. The CALLY index, derived from preoperative hematological parameters, may serve as a predictive marker for such complications.ObjectivesTo assess the association between preoperative inflammatory status via the CALLY index and the occurrence of postoperative pneumonia in patients with resectable ESCC.MethodsA retrospective cohort study was conducted from January 2020 to December 2022 at The Affiliated Huai’an No. 1 People’s Hospital of Nanjing Medical University. A total of 215 patients who met inclusion criteria were analyzed. Clinical data, including CALLY indices calculated preoperatively, were collected. Propensity score matching was applied to minimize confounding biases. The predictive value of the CALLY index was assessed using receiver operating characteristic analysis, and logistic regression was used to identify factors associated with postoperative pneumonia.ResultsROC curve analysis demonstrated the CALLY index had an area under the curve of 0.764 for predicting postoperative pneumonia, with a cutoff value of 1.97 achieving 67.69% sensitivity and 84.67% specificity. In multivariate analysis, a lower CALLY index was significantly associated with increased pneumonia risk, independent of other factors (adjusted OR = 0.66, p < 0.001). High CALLY index scores correlated with a decreased likelihood of postoperative pneumonia, reinforcing its utility as a non-invasive prognostic marker.ConclusionsThe CALLY index is a robust, independent predictor of postoperative pneumonia in patients with resectable ESCC. Preoperative assessment of this index could enhance risk stratification and guide proactive management strategies to improve postoperative outcomes.